Placenta Accreta Spectrum Outcomes Using Tourniquet and Forceps for Vascular Control - Huang, Jingrui; Zhang, Xiaowen; Liu, Lijuan; Duan, Si; Pei, Chenlin; Zhao, Yanhua; Liu, Rong; Wang, Weinan; Jian, Yu; Liu, Yuelan; Liu, Hui; Wu, Xinhua; et al. (Frontiers in Medicine, 2021)
Objective: To evaluate the use of tourniquet and forceps to reduce bleeding during surgical treatment of severe placenta accreta spectrum (placenta increta and placenta percreta). Methods: A tourniquet was used in the lower part of the uterus during surgical treatment of severe placenta accreta spectrum. Severe placenta accreta spectrum was classified into two types according to the relative position of the placenta and tourniquet during surgery: upper-tourniquet type, in which the entire placenta was above the tourniquet, and lower-tourniquet type, in which part or all of the placenta was below the tourniquet. The surgical effects of the two types were retrospectively compared. We then added forceps to the lower-tourniquet group to achieve further bleeding reduction. Finally, the surgical effects of the two types were prospectively compared. Results: During the retrospective phase, patients in the lower-tourniquet group experienced more severe symptoms than did patients in the upper-tourniquet group, based on mean intraoperative blood loss (upper-tourniquet group 787.5ml, lower-tourniquet group 1434.4ml) intensive care unit admission rate (upper-tourniquet group 1.0%, lower-tourniquet group 33.3%), and length of hospital stay (upper-tourniquet group 10.2d, lower-tourniquet group 12.1d). During the prospective phase, after introduction of the revised surgical method involving forceps (in the lower-tourniquet group), the lower-tourniquet group exhibited improvements in the above indicators (intraoperative average blood loss 722.9ml, intensive care unit admission rate 4.3%, hospital stays 9.0d). No increase in the rate of complications was observed. Conclusion: The relative positions of the placenta and tourniquet may influence the perioperative risk of severe placenta accreta spectrum. The method using a tourniquet (and forceps if necessary) can improve the surgical effect in cases of severe placenta accreta spectrum.